The Effectiveness of the Aswat Arabiyah Strategy in Improving Imla' Learning Outcomes for Class VIII MTs Al-Jauhar Duri - Mohd Fikri Azhari; Indah Sari; Henrizal Hadi (Lisanan Arabiya: Jurnal Pendidikan Bahasa Arab, 2022)
The purpose of this study was to determine the application of the Ashwat Arabiyah strategy in learning Imla 'to improve the writing skills of class VIII students at MTs Al-Jauhar Duri and to find out the improvement in the achievement results of class VIII students at MTs Al-Jauhar Duri in Arabic writing skills after receiving the Ashwat Arabiyah strategy. This research was conducted at Pondok Modern Al-Jauhar Duri, Jalan Asrama Tribrata, Pematang Pudu Village, Mandau District, Bengkalis Regency. The sample used was 1 Imla' teacher and 26 students of class VIII.C. This study uses a classroom action research design (PTK), which is research conducted in the classroom by observing activities that are intentionally raised and occur in a class. The research procedure consists of planning, implementing, observing, and reflecting. Based on the results, it is known that the initial condition of the ability of class VIII MTs Al-Jauhar Duri in learning Imla 'is low, most of them have not been able to distinguish hijaiyah letters and connect them in a sentence. This is evidenced by the results of the pre-cycle average ability of 11, 53% of students. Meanwhile, the writing ability in learning Imla' Class VIII MTs Al-Jauhar Duri can be improved by using the Ashwat Arabiyah strategy, this is evidenced from the results of the pre-cycle the average ability of students is 11.53%, in the first cycle the average ability of students is 15,38%, in the second cycle the average ability of students is 65.38%, and in the third cycle the average ability of students is 73.07%. This shows that there is a positive impact from the implementation of the Ashwat Arabiyah strategy in improving the writing ability of VIII grade students at MTs Al-Jauhar Duri with an indicator of success in cycle III as much as 73.07%.